Projection displays. - Brennesholtz, Matthew S., 1947-; Stupp, Edward H., ....- (Chichester : Wiley, 2008)
1 Introduction 2 Markets and Applications 3 Emissive Image Sources 4 Liquid Crystal Light Valves and Microdisplays 5 Micro-electromechanical Devices 6 Filters, Integrators and Polarization Components 7 Projection Lenses and Screens 8 Light Sources for Light-valve and Microdisplay Projection Systems 9 Scanned Projection Systems 10 Microdisplay System Architectures 11 Modeling Lumen Output 12 Projector Lumen Throughput 13 Characteristics and Characterization 14 Image Artifacts
Keywords: Projectoren